Facile synthesis of hydroxyapatite from bovine bone and gelatin/chitosan‐hydroxyapatite scaffold for potential tissue engineering application. Issue 2 (17th April 2022) - Anh, Nguyen Thi Hong; Trinh, Tra Phuong; Tan, Le Van; Tho, Nguyen Thi Mai; Van Cuong, Nguyen
Abstract: Here, hydroxyapatite was obtained from bovine bones by thermal decomposition at temperatures from 550 to 850°C at the time of 5 hours. The physical characterization showed that all organic components in the bovine bones were eliminated and produced the clean hydroxyapatite. Composite scaffolds were made of the gelatin (G), chitosan (C), and hydroxyapatite (HAp) in various gelatin/chitosan‐HAp mass ratios by the freeze‐drying method. The FT‐IR, SEM, XRD, and EDX techniques were used to examine the structures of synthetic HAp and composite scaffolds. XRD showed three main peaks at 2θ = 31.8, 33.1, and 40.1 o, which resembled the characteristic peaks of hydroxyapatite and approved the formation of HAp at 850°C. FT‐IR results at 1360 and 1554 cm ‐1 confirmed the formation of –C=N‐ bond of the interaction between chitosan and gelatin to form a 3D interconnected network in scaffolds. The swelling and in‐vitro degradation of composite scaffolds were carried out in PBS and 10 %FBS + PBS solutions. All composite scaffolds demonstrated the cell viability of L929 was above 95 %. These results indicated that the composite showed a potential application in tissue engineering.